2013
DOI: 10.1186/1471-2490-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma of the urinary bladder: a systematic review of the contemporary literature

Abstract: BackgroundPheochromocytoma (paraganglioma) of the urinary bladder is a rare tumor. Herein we sought to review the contemporary literature on pheochromocytomas of the urinary bladder in order to further illustrate the presentation, treatment options and outcomes of patients diagnosed with these tumors.MethodsA comprehensive review of the current literature was conducted according to the PRISMA guidelines by accessing the NCBI PubMed database and using the search terms “paraganglioma, pheochromocytoma, bladder.”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
131
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 63 publications
2
131
0
2
Order By: Relevance
“…Initial presentation is extremely varied in these tumors, necessitating a low threshold of suspicion in the face of hypertension or hematuria. Beilan et al [1] extensively reviewed the English literature on this subject and reported the largest analysis of pheochromocytomas involving the urinary bladder. A total of 106 patients included in their own study were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial presentation is extremely varied in these tumors, necessitating a low threshold of suspicion in the face of hypertension or hematuria. Beilan et al [1] extensively reviewed the English literature on this subject and reported the largest analysis of pheochromocytomas involving the urinary bladder. A total of 106 patients included in their own study were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment modality for localized or locally advanced pheochromocytomas is surgery, while metastatic or recurrent tumors are treated with palliative therapy [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PUBs, since first reported in 1953, represent less than 1% of all pheochromocytomas and less than 0.05% of all bladder tumors, though the bladder is the most common extra ganglionic location for pheochromocytoma [1,2]. The optimal treatment for PUB is partial cystectomy.…”
Section: Introductionmentioning
confidence: 99%